Best practice workplace negotiations - Luecke, Richard (American Management Association, 2010)
Best Practice Workplace Negotiations offers a systematic approach to developing negotiating skills. It serves as an introduction to current best practices in negotiation that can be applied across a broad range of business situations. This up-to-the-minute course covers win-win vs. win-lose negotiations; the BATNA concept (best alternative to a negotiated agreement-what every negotiator should have in his mind before entering into any negotiation); walk-away price, or reserve point; negotiation as a logical set of process steps-preparation, initial moves, application of tactics, and post-deal.